Estimation of Overdiagnosis of Lung Cancer in Low-Dose Computed Tomography Screening: A Secondary Analysis of the Danish Lung Cancer Screening Trial - Heleno, Bruno (JAMA Intern Med, 2018)
This study analyzes data from the Danish Lung Cancer Screening Trial to determine the amount of overdiagnosis of computed tomography–detected lung cancer.